2019
DOI: 10.1111/rda.13426
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of high‐ and low‐fertile buffalo bull spermatozoa for identification of fertility‐associated proteins

Abstract: Contents The present study identified few potential proteins in the spermatozoa of buffalo bulls that can be used as an aid in fertility determination through comparative proteomics. The sperm proteome of high‐fertile buffalo bulls was compared with that of low‐fertile buffalo bulls using two‐dimensional difference gel electrophoresis (2D‐DIGE), and the differentially expressed proteins were identified through mass spectrometric method. The protein interaction network and the functional bioinformatics analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…We found different candidate genes by analyzing these GO terms, and some of these genes, such as ATM serine/threonine kinase ( ATM ), glycogen synthase kinase 3 beta ( GSK3B ), and cyclin A1 ( CCNA1 ), were found to be significantly enriched in the cell cycle pathway and associated with spermatozoa differentiation. The ATM protein is associated with low-fertile buffalo bull spermatozoa ( M. K et al, 2019 ); in mouse spermatocytes, the meiotic recombination is initiated by SPO11-induced double-strand breaks (DSBs) , and ATM controls this process ( Huang et al, 2019 ; Paiano et al, 2020 ). GSK3B showed significant expression changes across these pubertal stages in the hypothalamus of piglets and is also involved in crucial biological processes that regulate economically relevant traits associated with beef cattle fertility ( Fonseca et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found different candidate genes by analyzing these GO terms, and some of these genes, such as ATM serine/threonine kinase ( ATM ), glycogen synthase kinase 3 beta ( GSK3B ), and cyclin A1 ( CCNA1 ), were found to be significantly enriched in the cell cycle pathway and associated with spermatozoa differentiation. The ATM protein is associated with low-fertile buffalo bull spermatozoa ( M. K et al, 2019 ); in mouse spermatocytes, the meiotic recombination is initiated by SPO11-induced double-strand breaks (DSBs) , and ATM controls this process ( Huang et al, 2019 ; Paiano et al, 2020 ). GSK3B showed significant expression changes across these pubertal stages in the hypothalamus of piglets and is also involved in crucial biological processes that regulate economically relevant traits associated with beef cattle fertility ( Fonseca et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Domestic animal proteomics has also been applied to animal production systems related to different aspects of lactation. These included the study of lactating mammary epithelial cells in cattle and water buffalo [57,58], bovine milk proteome characterization and differentiation between breeds [59,60] or the establishment of protein biomarkers for early pregnancy diagnosis [61] estrus detection [62], male fertility [63,64].…”
Section: Domestic Animal Proteomics In India In Recent Yearsmentioning
confidence: 99%
“…Earlier studies indicated that several molecules including Adenylate kinase 1 (Kasimanickam et al, 2012), ATP5D (Aslam et al, 2018), CatSper (Qi et al, 2007;Singh & Rajender, 2015), Cytochrome P450 aromatase (Aslam et al, 2014), MDH2 (Aslam et al, 2018) and Phosphatidylethanolamine-binding protein (Arangasamy et al, 2011; Somashekar et al, 2017) have been shown to be associated with sperm fertility. Very recently, it was reported that molecules related to energy metabolism and capacitation were altered in low-fertile buffalo spermatozoa (Aslam et al, 2019).…”
Section: Alterations In Expression Of Sperm Molecules During Differentmentioning
confidence: 99%